Socioeconomic and Demographic Risk Factors of Child Sexual Abuse in Pakistan: A Case Study of Khyber Pakhtunkhwa Province - Zareena; Nazir, Naila; Ali, Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
Child sexual abuse is a harsh reality and a threat of harm to children. Pakistan’s high population growth and increasing poverty has resulted in child labor on streets. Children are exposed to all forms of abuse including sexual exploitation. The main objective of this study is to find out the risk factors of child sexual abuse. The present study has been conducted in the capital city of Khyber Pakhtunkhwa province, Pakistan. The respondents have been selected from places where children are found most often, selling products, or wondering in search of jobs. Primary data was collected through semi-structured questionnaire using snowball sampling. The total response was found at 50, including Pakistani and Afghan refugees’ children. According to the results 76% children are deprived of their parents’ proper attention, 96% are very poor and just earning below Rs. 8000, 66% are in the age group of 8 to 12 years, 72% of the respondents have only one room in their house, 78% respondents are not enrolled in school; about 22 % sample respondents left the school early, 64% of the respondent having large family size (family members more then 6), and 98% of the victims were out of homes for earnings. It is concluded that the main risk factors of child abuse consist of poverty, child labor, large family size, school dropout, and low parental warmth. With respect to most of the variables, no significant difference was found between the two nationals.